Kinetics and mechanism of the early stages of the voltammetric electrooxidation of carbon monoxide preadsorbed on polycrystalline platinum in acid electrolyte - Bilmes, Sara Aldabe (1986)
The first stages of the electrooxidation of CO previously adsorbed on polycrystalline Pt in 1 M HClO4 at 25°C were investigated by means of the triangularly modulated triangular potential sweep technique. Runs were made with a Pt surface covered either partially or completely with adsorbed CO over a wide range of frequency and amplitude of the modulating signal. Reactions between the strongly and the weakly bonded adsorbed oxygen-containing adsorbed species with the linear and the bridge forms of adsorbed CO were followed via the voltammetric measurements. The kinetics of the various possible processes are discussed in terms of previous results on the voltammetric electrooxidation of adsorbed CO and on the early stages of O-electroadsorption on Pt. CO adsorption on Pt produces a change in the apparent electrode capacity which is interpreted in terms of the structure of the inner part of the electrical double layer.